2019
DOI: 10.1186/s40425-019-0718-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-dose radiation on abscopal responses in patients receiving high-dose radiation and immunotherapy

Abstract: Background Preclinical evidence suggests that low-dose radiation may overcome the inhibitory effects of the tumor stroma and improve a tumor’s response to immunotherapy, when combined with high-dose radiation to another tumor. The aim of this study was to evaluate tumor responses to this combination in a clinical setting. Methods A post-hoc analysis of 3 ongoing immunoradiation trials was performed. Twenty-six (of 155) patients received low-dose radiation (1–20 Gy total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 18 publications
2
89
0
Order By: Relevance
“…The post hoc analysis of our recently completed phase II trial of ipilimumab (anti-CTLA-4), in which stereotactic radiation therapy was given to lung or liver metastases, showed that tumors near the targets that received low-dose scatter radiation had significantly higher response rates (31%) compared with distant tumors that did not receive radiation (5%). 38 While both prior retrospective studies 16 38 and the present study provide exciting evidence for the therapeutic potential of L-XRT, a prospective randomized trial is warranted to confirm the role of L-XRT. In some of the patient cases we report here, there was regrowth of the tumors, suggesting delayed immune evasion.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The post hoc analysis of our recently completed phase II trial of ipilimumab (anti-CTLA-4), in which stereotactic radiation therapy was given to lung or liver metastases, showed that tumors near the targets that received low-dose scatter radiation had significantly higher response rates (31%) compared with distant tumors that did not receive radiation (5%). 38 While both prior retrospective studies 16 38 and the present study provide exciting evidence for the therapeutic potential of L-XRT, a prospective randomized trial is warranted to confirm the role of L-XRT. In some of the patient cases we report here, there was regrowth of the tumors, suggesting delayed immune evasion.…”
Section: Discussionmentioning
confidence: 69%
“…To date, we have treated more than 25 patients on various trial arms with H-XRT, L-XRT, and immunotherapy to promote secondary tumor response. 16 Two representative cases from our recent prospective trial (NCT02710253) are demonstrated here ( figure 5A and online supplemental figure S9 ), followed by the tumor growth curves of nine patient cases that received RadScopal treatment from the same trial ( figure 5B and table 1). Patient 1 in figure 5A was a 54-year-old man with metastatic human papillomavirus-positive oropharyngeal squamous cell carcinoma who initially reported partial response to anti-PD1 therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the biological context remains to be proven that would favor multiple rounds of high-end ablative dose schedules in oligometastatic patient as advocated by some groups (49). Another concept of potential clinical relevance that has been put forward is the possibility that the immunomulatory effect of low-dose radiation for stromal modulation could favor T cell infiltration and enhance the immune response (47,50).…”
Section: Addressing the Evasive Objective Of Durable Responses Of Radmentioning
confidence: 99%